Mammalian ISWI gene knockdown modulates growth and differentiation properties of neural progenitor cells - Rennick, Stephen D (University of Ottawa (Canada), 2008)
Epigenetic modifications during cellular differentiation are critical for establishing the expression of tissue specific genes characterizing particular cell types. There are two groups of chromatin modifying enzymes that regulate these processes, the ATP-dependent complexes, and the histone modifying complexes. In ATP-dependent remodelling complexes, the imitation switch (ISWI) group has been studied extensively in the past. ISWI proteins were initially discovered in Drosophila and mammals contain two orthologs called SNF2H and SNF2L. Past experiments demonstrated that these remodelers have distinct roles in cellular differentiation and proliferation SNF2H expression is greatest in proliferating neuroprogenitor populations, whereas SNF2L predominates in mature neurons. Additionally, SNF2H null mice are periimplantation lethal due to defective cellular proliferation. Other studies showed that neuronal cell cultures ectopically expressing increased levels of SNF2L display a dramatic increase in neurite extension and spontaneous differentiation. These findings point to requirements for SNF2L during neuronal differentiation but the distinct manner in which ISWI proteins oversee this process remains unknown. To elucidate the role of ISWI proteins in the regulation of neuronal proliferation and differentiation we used shRNA transfection to stably knockdown the genes of interest in established neuronal cell lines. Concurrently, we examined the growth and differentiation properties of primary neuronal cultures derived from mice functionally ablated for Snf2l. Results in neuroblastoma cultures show that upon Snf2l knockdown proliferation is maintained in 30% of the population under differentiation conditions at 4 days of differentiation. In contrast, Snf2H knockdown cells proliferate normally but undergo extensive apoptosis when induced to differentiate. Aberrant cell replication was also observed in E14.5 and E12.5 neurosphere cultures and resulted in a 2-fold decrease in the number of neurons generated and a 4-fold reduction in astrocyte production at 4 days of differentiation. Moreover, both astrocytes and neurons expressing differentiation markers had reduced neurite extensions and branching patterns suggesting a distinct developmental delay. Taken together these studies define distinct roles for ISWI in growth and differentiation of CNS cells.
Keywords: Biology, Molecular.; Biology, Cell.; Health Sciences, Immunology.